Continuous preparation method of high-strength titanium carbide guided bone regeneration film
Through the roll-to-roll auxiliary scraping method combined with hydrogen bond and ion bond crosslinking, a high-strength titanium carbide-guided bone regeneration film was successfully prepared, which solved the problem of insufficient material strength and bone regeneration performance in the prior art, and achieved high strength and Excellent bone regeneration effect.
Patent Information
- Application Number
- CN202411378977.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-17
AI Technical Summary
It is difficult to continuously prepare high-strength titanium carbide-guided bone regeneration films in the prior art, and the induced bone regeneration performance of the interface crosslinking agent has not been fully considered, which limits the practical application of the material.
The coil-to-roll auxiliary scraping method is used to combine hydrogen bond and ion bond cross-linking. By vortexing the Ti3C2Tx and sericin blending aqueous solution at room temperature, the sericin is uniformly adsorbed on the surface of Ti3C2Tx nanosheets to form a hydrogen bond cross-linking composite film. Further ionic bond cross-linking is performed in aqueous zinc chloride solution.
High strength, excellent tensile strength, Young's modulus and toughness were achieved, and the bone regeneration performance in the body was significantly improved. The ratio of the volume of new bone to the total volume of bone defect areas reached 70.1~77.4%.
Smart Images

Figure CN119139541A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a continuous preparation method of a high-strength titanium carbide film for guiding bone regeneration, and belongs to the field of preparation of biomedical nanocomposite materials. Background Art
[0002] Titanium carbide (Ti3C2T x ) nanosheets have excellent mechanical (Sci. Adv. 2018, 4, eaat0491.) and bone regeneration induction (Int. J. Nanomed. 2019, 14, 10091.) properties and have broad application prospects in aerospace and biomedical fields. Therefore, it is necessary to convert Ti3C2T x Nanosheets are continuously assembled into macroscopic high-performance Ti3C2T x Nanocomposite materials.
[0003] At present, Ti3C2T x Methods for assembling nanosheets into macroscopic films include blade coating (Adv. Mater. 2020, 32, 2001093.), drop coating (Matter 2020, 3, 546.) and slot die coating (Adv. Funct. Mater. 2023, 33, 2213183.). However, due to the high molecular weight of Ti3C2T x There are pores between nanosheets and the interface interaction is weak. The Ti3C2T prepared by these methods x Thin films usually have low mechanical properties, which limits their practical applications.
[0004] In recent years, scientists have used various interfacial cross-linking strategies to improve the performance of Ti3C2T x Mechanical properties of thin films. For example, Cao et al. (ACS Nano 2018, 12, 4583.) x Nanocellulose was introduced between the layers to prepare highly conductive Ti3C2T through hydrogen bonding. x Composite film; Ding et al. (Nat. Sustain. 2020, 3, 296.) on Ti3C2T x The introduction of aluminum ions between the layers improves the Ti3C2T x Anti-swelling stability of thin films in water; Lee et al. (ACS Nano 2020, 14, 11722.) in Ti3C2T x The introduction of polydopamine between the layers improves the Ti3C2T x The tensile strength and toughness of the film. Recently, Cheng Qunfeng et al. (Science 2021, 374, 96.) studied the tensile strength and toughness of Ti3C2Tx The introduction of sodium carboxymethyl cellulose and sodium tetraborate crosslinkers between the layers effectively eliminated the pores and greatly improved the Ti3C2T x These strategies can improve the mechanical properties of Ti3C2T x The mechanical properties of the film are very good, but it is difficult to continuously prepare Ti3C2T x Thin films are rarely considered, and the bone regeneration-inducing performance of interfacial crosslinkers is rarely considered, which limits practical applications. Therefore, it is necessary to develop a continuous preparation method for high-strength Ti3C2T x New technology for guided bone regeneration membranes. To date, there are no literature or patent reports on the continuous preparation of high-strength titanium carbide guided bone regeneration membranes using roll-to-roll assisted scraping combined with hydrogen bonds and ionic bonds for orderly cross-linking. Summary of the invention
[0005] The technology of the present invention solves the problem: Overcoming the deficiencies of the prior art, providing a continuous preparation method for a high-strength titanium carbide guided bone regeneration film, wherein the prepared film has excellent tensile strength, Young's modulus, toughness and bone regeneration performance.
[0006] The present invention is achieved by the following technical scheme: a continuous preparation method of a high-strength titanium carbide guided bone regeneration film, firstly vortex oscillating Ti3C2T x The aqueous solution of SS was mixed with sericin (SS) to make SS uniformly adsorbed on Ti3C2T through hydrogen bonding. x The surface of the nanosheets; then the roll-to-roll assisted scraping method is used to continuously assemble the uniformly mixed aqueous solution into a hydrogen-bonded cross-linked titanium carbide (HBM) composite film; finally, the HBM composite film is immersed in a zinc chloride (ZnCl2) aqueous solution to obtain a hydrogen-bonded and ionic-bonded orderly cross-linked titanium carbide (SBM) composite film. The specific implementation steps are as follows:
[0007] (1) Ti3C2T was stirred by ultrasonic method at room temperature. x and SS were mixed into uniform Ti3C2T x aqueous solution and SS aqueous solution, the Ti3C2T x The aqueous solution contains Ti3C2T x Nanosheets;
[0008] (2) The Ti3C2T obtained in step (1) x The aqueous solution and the SS aqueous solution were mixed and vortexed to make SS uniformly adsorbed on the Ti3C2T x The surface of the nanosheets was uniformly mixed with the aqueous solution;
[0009] (3) vacuum-debubbling the mixed aqueous solution obtained in step (2), and then continuously assembling the mixed aqueous solution into an HBM composite film by a roll-to-roll assisted doctor blade coating method;
[0010] (4) Immerse the HBM composite film obtained in step (3) in a ZnCl2 aqueous solution, wash and dry to obtain a SBM composite film.
[0011] Furthermore, in step (1), Ti3C2T x The concentrations of aqueous solutions of Ti3C2T4 and SS are both 20~60 mg / mL. x The concentrations of the aqueous solution and the SS aqueous solution were 20 mg / mL, 25 mg / mL, 30 mg / mL, 35 mg / mL, 40 mg / mL, 45 mg / mL, 50 mg / mL, 55 mg / mL or 60 mg / mL.
[0012] Furthermore, in the step (1), the stirring time is 5 to 15 min (e.g., 5 min, 7 min, 10 min or 15 min), the ultrasonic time is 1 to 2 min (e.g., 1 min, 1.5 min or 2 min), and the ultrasonic power in the ice water bath is 50 to 70 W (e.g., 50 W, 60 W or 70 W), so that the Ti3C2T x In the case of nanosheets and SS structures, uniform dispersion of Ti3C2T x Nanosheets and SS.
[0013] Furthermore, in step (2), the Ti3C2T x The mass ratio of nanosheets to SS is 3-20. Too little SS will not be able to completely cover Ti3C2T x Nanosheets, too much SS will be x Excessive deposition on the surface of the nanosheets, both of which are not conducive to the subsequent zinc ion (Zn 2+ ) with SS and Ti3C2T x Nanosheets are cross-linked. For example, in step (2), the Ti3C2T x The mass ratio of nanosheets to SS is 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 14, 16, 18, or 20.
[0014] Furthermore, in step (2), the vortex oscillation speed is 1000-2000 rpm (for example, 1000 rpm, 1500 rpm or 2000 rpm) and the time is 3-5 min, which not only makes SS uniformly adsorbed on Ti3C2T x Nanosheet surface, and ensure Ti3C2Tx The nanosheet structure does not break.
[0015] Furthermore, in the step (3), the process of vacuum degassing is to place the mixed aqueous solution in a closed desiccator, evacuate to a vacuum degree of 1000-3000 Pa, and maintain this vacuum degree for 2-4 minutes, and then release the air, and repeat the above vacuuming and releasing process 10-15 times to completely remove the bubbles in the mixed aqueous solution.
[0016] Furthermore, in the step (3), a roll-to-roll assisted scraping method is used, and the specific implementation process includes:
[0017] (31) The mixed aqueous solution after vacuum degassing is continuously extruded through a syringe pump and dripped onto the substrate surface of the coating machine;
[0018] (32) Adjust the distance between the scraper and the substrate to 0.2-3 mm, fix the scraper, and then start the substrate unwinding and winding device for scraping, and the substrate conveying rate is greater than 10 cm / min (for example, the substrate conveying rate is 11 cm / min, 12 cm / min, 13 cm / min, 15 cm / min or 20 cm / min);
[0019] (33) The substrate with the mixed aqueous solution coated on its surface is continuously conveyed through a heater at a temperature of 40–50 °C to dry and remove moisture, and then continuously rolled up to obtain an HBM composite film.
[0020] Furthermore, in the step (4), the concentration of the ZnCl2 aqueous solution is 5 to 100 mg / mL (for example, the concentration of the ZnCl2 aqueous solution is 5 mg / mL, 6 mg / mL, 10 mg / mL, 15 mg / mL, 20 mg / mL, 25 mg / mL, 30 mg / mL, 35 mg / mL, 40 mg / mL, 45 mg / mL, 50 mg / mL, 55 mg / mL, 60 mg / mL, 65 mg / mL, 70 mg / mL, 75 mg / mL, 80 mg / mL, 85 mg / mL, 90 mg / mL, 95 mg / mL or 100 mg / mL). Too low a concentration of ZnCl2 cannot react with SS and Ti3C2T x The nanosheets are fully cross-linked, while too high a concentration of ZnCl2 will react with SS and Ti3C2T xThe nanosheets are over-crosslinked, both of which are not conducive to improving the mechanical properties of the SBM composite film. The preferred concentration range is 10-40 mg / mL. In order to better optimize the performance of the SBM composite film, the concentrations of the ZnCl2 aqueous solution are selected as 10 mg / mL, 20 mg / mL, 40 mg / mL, and 80 mg / mL, respectively. The corresponding four SBM composite films are marked as SBM-I, SBM-II, SBM-III, and SBM-IV, respectively; the immersion time in the ZnCl2 aqueous solution is 20-40 min (for example, 20 min, 25 min, 30 min, 35 min, or 40 min) to make the Zn 2+ Fully penetrate into the film to cause cross-linking.
[0021] Furthermore, in step (4), the washing step is performed by soaking the uncrosslinked Zn 2+ Completely remove; the drying process is to vacuum dry at 40~50 °C for 20~30 min to completely remove the free water molecules adsorbed in the film.
[0022] Furthermore, in step (4), the Zn 2+ The content is 0.4~2.6 wt%. For example, the Zn content of the prepared SBM composite film is 2+ The content is 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1.1 wt%, 1.3 wt%, 1.5 wt%, 1.7 wt%, 1.9 wt%, 2.1 wt%, 2.3 wt%, 2.5 wt% or 2.6 wt%.
[0023] Furthermore, in step (4), the thickness of the SBM composite film obtained is 1 to 20 μm. For example, the thickness of the SBM composite film obtained is 1 μm, 1.2 μm, 1.5 μm, 1.7 μm, 1.9 μm, 2.1 μm, 2.3 μm, 2.5 μm, 2.7 μm, 2.9 μm, 3.1 μm, 3.5 μm, 4 μm, 6 μm, 8 μm, 12 μm, 15 μm, 18 μm or 20 μm.
[0024] Principle of the invention: Ti3C2T by roll-to-roll assisted scraping x The composite film is prepared continuously. During the preparation process, biocompatible SS molecules that can remove active oxygen and active nitrogen are introduced into the hydrogen bond cross-linking and Zn 2+ Ionic bond cross-linking greatly improves Ti3C2T xMechanical and in vivo bone regeneration properties of composite films, thereby continuously preparing high-strength Ti3C2T x Guided bone regeneration film, prepared with existing Ti3C2T x Compared with the technology of composite film, the characteristics and advantages of the present invention are:
[0025] (1) SS has good biocompatibility and contains a large number of phenolic hydroxyl groups on its molecular chain, which can remove reactive oxygen and reactive nitrogen in the bone defect area, thus reacting with Ti3C2T in the body. x Nanosheets synergistically resist inflammation, induce M2 macrophage differentiation, and promote osteogenesis. In addition, SS molecules can react with Ti3C2T x The nanosheets form hydrogen bonds and fill Ti3C2T x Interlayer pores, improve Ti3C2T x Mechanical properties of composite films;
[0026] (2) Zn 2+ Can be combined with SS molecules and Ti3C2T x The nanosheets form ionic cross-links, further eliminating the Ti3C2T x Interlayer pores, improve Ti3C2T x Mechanical properties of composite films;
[0027] (3) The SBM composite film has a strong interfacial effect and a dense structure, which can maintain good structural integrity in the body and prevent fibroblasts from invading the bone defect area, thereby providing sufficient space for bone regeneration;
[0028] (4) Combining roll-to-roll assisted scraping with hydrogen bonding and ionic bonding ordered cross-linking strategies to achieve high-strength Ti3C2T x Continuous preparation of membranes for guided bone regeneration.
[0029] Therefore, the SBM composite film prepared continuously in the present invention not only has ultra-high tensile strength (641-755 MPa), high Young's modulus (29.2-36.6 GPa) and high toughness (13.9-17.4 MJ / m 3 ), and has excellent in vivo bone regeneration performance. After being implanted as a guided bone regeneration membrane into the skull defect area of rats for 8 weeks, the ratio of the new bone volume to the total volume of the bone defect area was 70.1~77.4%. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] FIG1 shows the continuous preparation process of high-strength SBM guided bone regeneration film, which includes: firstly, vortex oscillation obtained uniform SS and Ti3C2T xThe mixed aqueous solution is continuously assembled into an HBM composite film by roll-to-roll assisted doctor blade coating; then the HBM composite film is immersed in a ZnCl2 aqueous solution, and the SBM composite film is obtained after washing and drying.
[0031] Figure 2 shows the uncrosslinked Ti3C2T x (MXene), HBM, ionically cross-linked Ti3C2T x (IBM) and infrared spectra of SBM-II films, compared with MXene films (3432 cm -1 ), the -OH peaks of HBM and IBM composite films red-shift to 3416 cm -1 and 3422 cm -1 , which is mainly due to the cross-linking effects of hydrogen bonds and ionic bonds. In addition, the -OH peak of the SBM-II film further red-shifts to 3410 cm -1 , indicating the orderly cross-linking effect of hydrogen bonds and ionic bonds.
[0032] Figure 3 shows the pore structures of MXene and SBM-II films reconstructed by nano-X-ray tomography (Nano-CT) 3D. Compared with MXene film, SBM-II film has fewer pores and a denser structure.
[0033] Figure 4 shows the tensile stress-strain curves of MXene and SBM-II films.
[0034] Figure 5 shows the micron X-ray tomography (Micro-CT) three-dimensional reconstruction photos of the skull samples 8 weeks after the MXene and SBM-II films were implanted into the rat skull defect area as guided bone regeneration films. DETAILED DESCRIPTION
[0035] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. However, the following embodiments are limited to explaining the present invention, and the protection scope of the present invention should include the entire contents of the claims, and through the description of the following embodiments, those skilled in the art can fully implement the entire contents of the claims of the present invention.
[0036] As shown in FIG1 , the method of the present invention is implemented as follows: first, vortex oscillation is used to prepare uniform SS and Ti3C2T xThe blended aqueous solution is then continuously extruded and dripped onto the substrate surface of the coating machine through a syringe pump, and the distance between the scraper and the substrate is adjusted, the scraper is fixed, and then the substrate unwinding and winding device is started for scraping. The substrate with the blended aqueous solution on the surface is continuously conveyed through a heater with a temperature of 40-50 °C, dried to remove moisture, and then continuously rolled to obtain an HBM composite film; then the HBM composite film is immersed in a ZnCl2 aqueous solution to obtain an SBM composite film. By changing the concentration of the ZnCl2 aqueous solution, the Zn content in the SBM composite film can be regulated. 2+ content, thereby optimizing the mechanical properties of the SBM composite film. 2+ When the content of is 0.926 wt%, the mechanical properties of the SBM composite film are optimal, which is marked as SBM-II. The tensile strength of the SBM composite film is as high as 755 MPa, the corresponding Young's modulus is 32.9 GPa, and the toughness is 17.4 MJ / m 3 In addition, the SBM composite film also has excellent in vivo bone regeneration performance. After being implanted as a guided bone regeneration film into the skull defect area of rats for 8 weeks, the ratio of the new bone volume to the total volume of the bone defect area was 77.4%.
[0037] The parameter testing method of the following embodiments of the present invention is as follows:
[0038] The tensile strength, toughness and Young's modulus test method includes the following steps: (1) firstly, the film sample is cut into a rectangular sample strip of 3×10 mm; (2) then the sample strip is bonded to a paper frame with a hollowed-out center using epoxy resin, wherein the size of the paper frame is 15×25 mm, and the size of the central hollowed-out area is 5×10 mm. The sample strip is symmetrically fixed on the paper frame across the center of the hollowed-out area, and the 10 mm side of the sample strip, the 5 mm side of the hollowed-out area and the 25 mm side of the paper frame are parallel; (3) after the epoxy resin is cured, the paper frame is fixed on the fixture of the Sansi Zongheng UTM4103 universal mechanical testing machine, wherein the span is 5 mm; (4) then the two side frames of the hollowed-out area of the paper frame are cut off with scissors, and the universal mechanical testing machine software is started to perform a tensile mechanical property test, thereby obtaining the stress-strain curve of the sample strip, wherein the tensile rate is 1 mm / min, and the cross-sectional area of the sample strip is measured by the width (3 The tensile stress at the fracture point of the stress-strain curve, the integrated area, and the slope of the linear range of the initial elastic deformation are the tensile strength, toughness, and Young's modulus of the sample strip, respectively. (5) For each film sample, 3 to 5 sample strips were tested, and their tensile strength, toughness, and Young's modulus were the average values of the tensile strength, toughness, and Young's modulus of the corresponding 3 to 5 sample strips, respectively.
[0039] The in vivo bone regeneration performance test method includes the following steps: (1) 6-8 week old SD male rats were selected and purchased from Peking University Health Science Center. After the rats were anesthetized, the skin was cut open, the muscles and periosteum were separated, the bone surface was exposed, and a circular defect with a diameter of 5 mm was prepared on both sides of the bone suture. Then, a circular film sample with a diameter of 5 mm was implanted and covered the bone defect area, and the muscles and skin were sutured in place. (2) The rats were euthanized 56 days after surgery, and the rat skull specimens were taken and fixed with 4% paraformaldehyde. Then, micro-CT scanning and new bone volume analysis were performed. The ratio of new bone volume to total bone defect volume was the in vivo bone regeneration performance of the sample. (3) Each film sample was subjected to 3-5 in vivo bone regeneration experiments, and its in vivo bone regeneration performance was the average value of the corresponding 3-5 experimental results.
[0040] The preparation methods of some raw materials used in the following examples and comparative examples of the present invention are as follows:
[0041] Ti3C2T x The preparation method of the nanosheets comprises the following steps: (1) taking 15 mL of concentrated hydrochloric acid (concentration of 12 mol / L) in a polytetrafluoroethylene reagent bottle, and then adding 5 mL of deionized water thereto to obtain a diluted hydrochloric acid solution; (2) weighing 1.6 g of lithium fluoride powder, adding it to the diluted hydrochloric acid solution under continuous stirring, and continuing to stir for 5 minutes to obtain an etching solution; (3) weighing 1.0 g of titanium aluminum carbide (Ti3AlC2) powder, adding it to the etching solution under continuous stirring, and then sealing the polytetrafluoroethylene reagent bottle, and placing it in a water bath at 50 °C for constant temperature stirring and reaction for 30 hours; (4) evenly placing the mixed solution after the reaction into 4 50 mL centrifuge tubes, and then adding 30 mL of deionized water to each centrifuge tube, and centrifuging at 3500 rpm for 5 minutes. min, remove the supernatant, repeat the above process of adding deionized water, centrifuging, and removing the supernatant 6 to 8 times until the supernatant appears dark green and the lower layer precipitates into a paste-like slurry; (5) add 30 mL of deionized water to the above paste-like slurry precipitate in each centrifuge tube, then vortex oscillate (2000 rpm) for 3 min, and then centrifuge at 1500 rpm for 20 min to collect the supernatant; (6) further centrifuge the supernatant collected in step (5) at 4000 rpm for 20 min, and then collect the precipitate after centrifugation. After vacuum drying, the precipitate is obtained to obtain Ti3C2T x Nanosheet powder.
[0042] Sericin (SS) powder was purchased from Huzhou Xintiansi Biotechnology Co., Ltd.
[0043] Example 1
[0044] Prepare 25 mg / mL Ti3C2Tx Aqueous solution: weigh 2.5 g of Ti3C2T x Nanosheets were added to 100 mL of deionized water, mechanically stirred for 10 min, and then dispersed in an ice-water bath with ultrasound (60 W) for 1.5 min; 25 mg / mL SS aqueous solution was prepared by weighing 2.5 g of SS powder, adding it to 100 mL of deionized water, mechanically stirring it for 10 min, and then dispersing it in an ice-water bath with ultrasound (60 W) for 1.5 min; 10 mg / mL ZnCl2 aqueous solution was prepared by weighing 10 g of ZnCl2, adding it to 1000 mL of deionized water, mechanically stirring it for 10 min, and then dispersing it in an ice-water bath with ultrasound (60 W) for 2 min; then Ti3C2T x The aqueous solution and the SS aqueous solution were mixed in a volume ratio of 90:10; after vortex oscillation (1500 rpm) for 4 min, the uniformly mixed aqueous solution was placed in a closed desiccator, evacuated to a vacuum degree of 2000 Pa, and maintained at this vacuum degree for 4 min, and then deflated, and the above evacuation and deflation process was repeated 12 times to completely remove the bubbles in the mixed aqueous solution; then the mixed aqueous solution was continuously extruded and dripped on the substrate surface of the coating machine through a syringe pump, and the distance between the scraper and the substrate was adjusted to 0.25 mm, the scraper was fixed, and then the substrate unwinding and winding device was started for scraping, the substrate transmission rate was adjusted to 12 cm / min, the temperature of the heater was 45 °C, and the HBM composite film was continuously wound; then the HBM film was immersed in the above-prepared ZnCl2 aqueous solution for 30 min, taken out and washed with deionized water for 40 min, and then dried in a vacuum oven (45 °C) for 25 min to obtain an SBM composite film, marked as SBM-I, and the thickness of the SBM-I composite film was 2.55 ± 0.10 μm.
[0045] The SBM-I composite film contains Zn 2+ The content of carbon is 0.483 wt%; the mechanical properties of 3 to 5 sample strips (3 × 10 mm) were tested, and the results showed that the tensile strength was 641 ± 32 MPa, the Young's modulus was 29.2 ± 2.8 GPa, and the toughness was 15.7 ± 0.7 MJ / m 3 In addition, the results of in vivo bone regeneration experiments showed that after 8 weeks of implantation into the skull defect area of rats as a guided bone regeneration membrane, the ratio of the new bone volume to the total volume of the bone defect area was 70.1 ± 2.3%.
[0046] Example 2
[0047] Prepare 25 mg / mL Ti3C2T x Aqueous solution: weigh 2.5 g of Ti3C2Tx Nanosheets were added to 100 mL of deionized water, mechanically stirred for 10 min, and then dispersed in an ice-water bath with ultrasound (60 W) for 1.5 min; 25 mg / mL SS aqueous solution was prepared by weighing 2.5 g of SS powder, adding it to 100 mL of deionized water, mechanically stirring it for 10 min, and then dispersing it in an ice-water bath with ultrasound (60 W) for 1.5 min; 20 mg / mL ZnCl2 aqueous solution was prepared by weighing 20 g of ZnCl2, adding it to 1000 mL of deionized water, mechanically stirring it for 10 min, and then dispersing it in an ice-water bath with ultrasound (60 W) for 2 min; then Ti3C2T x The aqueous solution and the SS aqueous solution were mixed in a volume ratio of 90:10; after vortex oscillation (1500 rpm) for 4 min, the uniformly mixed aqueous solution was placed in a closed desiccator, evacuated to a vacuum degree of 2000 Pa, and maintained at this vacuum degree for 4 min, and then deflated, and the above evacuation and deflation process was repeated 12 times to completely remove the bubbles in the mixed aqueous solution; then the mixed aqueous solution was continuously extruded and dripped on the substrate surface of the coating machine through a syringe pump, and the distance between the scraper and the substrate was adjusted to 0.25 mm, the scraper was fixed, and then the substrate unwinding and winding device was started for scraping, the substrate transmission rate was adjusted to 12 cm / min, the temperature of the heater was 45 °C, and the HBM composite film was continuously wound; then the HBM film was immersed in the above-prepared ZnCl2 aqueous solution for 30 min, taken out and soaked and washed with deionized water for 40 min, and then dried in a vacuum oven (45 °C) for 25 min to obtain an SBM composite film, marked as SBM-II, and the thickness of the SBM-II composite film was 2.52 ± 0.09 μm.
[0048] The SBM-II composite film contains Zn 2+ The content of carbon is 0.926 wt%; the mechanical properties of 3 to 5 sample strips (3 × 10 mm) were tested, and the results showed that the tensile strength was 755 ± 22 MPa, the Young's modulus was 32.9 ± 1.9 GPa, and the toughness was 17.4 ± 0.5 MJ / m 3 In addition, the results of in vivo bone regeneration experiments showed that after 8 weeks of implantation into the skull defect area of rats as a guided bone regeneration membrane, the ratio of the new bone volume to the total volume of the bone defect area was 77.4 ± 3.5%.
[0049] Example 3
[0050] Prepare 25 mg / mL Ti3C2T x Aqueous solution: weigh 2.5 g of Ti3C2T xNanosheets were added to 100 mL of deionized water, mechanically stirred for 10 min, and then dispersed in an ice-water bath with ultrasound (60 W) for 1.5 min; 25 mg / mL SS aqueous solution was prepared by weighing 2.5 g of SS powder, adding it to 100 mL of deionized water, mechanically stirring it for 10 min, and then dispersing it in an ice-water bath with ultrasound (60 W) for 1.5 min; 40 mg / mL ZnCl2 aqueous solution was prepared by weighing 40 g of ZnCl2, adding it to 1000 mL of deionized water, mechanically stirring it for 10 min, and then dispersing it in an ice-water bath with ultrasound (60 W) for 2 min; then Ti3C2T x The aqueous solution and the SS aqueous solution were mixed in a volume ratio of 90:10; after vortex oscillation (1500 rpm) for 4 min, the uniformly mixed aqueous solution was placed in a closed desiccator, evacuated to a vacuum degree of 2000 Pa, and maintained at this vacuum degree for 4 min, and then deflated, and the above evacuation and deflation process was repeated 12 times to completely remove the bubbles in the mixed aqueous solution; then the mixed aqueous solution was continuously extruded and dripped on the substrate surface of the coating machine through a syringe pump, and the distance between the scraper and the substrate was adjusted to 0.25 mm, the scraper was fixed, and then the substrate unwinding and winding device was started for scraping, the substrate transmission rate was adjusted to 12 cm / min, the temperature of the heater was 45 °C, and the HBM composite film was continuously wound; then the HBM film was immersed in the above-prepared ZnCl2 aqueous solution for 30 min, taken out and washed with deionized water for 40 min, and then dried in a vacuum oven (45 °C) for 25 min to obtain an SBM composite film, marked as SBM-III, and the thickness of the SBM-III composite film was 2.53 ± 0.11 μm.
[0051] The SBM-III composite film contains Zn 2+ The content of carbon is 1.57 wt%; the mechanical properties of 3 to 5 sample strips (3 × 10 mm) were tested, and the results showed that the tensile strength was 699 ± 25 MPa, the Young's modulus was 34.4 ± 1.7 GPa, and the toughness was 15.2 ± 1.0 MJ / m 3 In addition, the results of in vivo bone regeneration experiments showed that after 8 weeks of implantation of the membrane into the skull defect area of rats as a guided bone regeneration membrane, the ratio of the new bone volume to the total volume of the bone defect area was 75.8 ± 1.6%.
[0052] Example 4
[0053] Prepare 25 mg / mL Ti3C2T x Aqueous solution: weigh 2.5 g of Ti3C2T xNanosheets were added to 100 mL of deionized water, mechanically stirred for 10 min, and then dispersed in an ice-water bath with ultrasound (60 W) for 1.5 min; 25 mg / mL SS aqueous solution was prepared by weighing 2.5 g of SS powder, adding it to 100 mL of deionized water, mechanically stirring it for 10 min, and then dispersing it in an ice-water bath with ultrasound (60 W) for 1.5 min; 80 mg / mL ZnCl2 aqueous solution was prepared by weighing 80 g of ZnCl2, adding it to 1000 mL of deionized water, mechanically stirring it for 10 min, and then dispersing it in an ice-water bath with ultrasound (60 W) for 2 min; then Ti3C2T x The aqueous solution and the SS aqueous solution were mixed in a volume ratio of 90:10; after vortex oscillation (1500 rpm) for 4 min, the uniformly mixed aqueous solution was placed in a closed desiccator, evacuated to a vacuum degree of 2000 Pa, and maintained at this vacuum degree for 4 min, and then deflated, and the above evacuation and deflation process was repeated 12 times to completely remove the bubbles in the mixed aqueous solution; then the mixed aqueous solution was continuously extruded and dripped on the substrate surface of the coating machine through a syringe pump, and the distance between the scraper and the substrate was adjusted to 0.25 mm, the scraper was fixed, and then the substrate unwinding and winding device was started for scraping, the substrate transmission rate was adjusted to 12 cm / min, the temperature of the heater was 45 °C, and the HBM composite film was continuously wound; then the HBM film was immersed in the above-prepared ZnCl2 aqueous solution for 30 min, taken out and soaked and washed with deionized water for 40 min, and then dried in a vacuum oven (45 °C) for 25 min to obtain an SBM composite film, marked as SBM-IV, and the thickness of the SBM-IV composite film was 2.56 ± 0.12 μm.
[0054] The SBM-IV composite film contains Zn 2+ The content of carbon is 2.51 wt%; the mechanical properties of 3 to 5 sample strips (3 × 10 mm) were tested, and the results showed that the tensile strength was 659 ± 13 MPa, the Young's modulus was 36.6 ± 1.3 GPa, and the toughness was 13.9 ± 0.1 MJ / m 3 In addition, the results of in vivo bone regeneration experiments showed that after 8 weeks of implantation into the skull defect area of rats as a guided bone regeneration membrane, the ratio of the new bone volume to the total volume of the bone defect area was 72.5 ± 1.9%.
[0055] Comparative Example 1
[0056] Prepare 25 mg / mL Ti3C2T x Aqueous solution: weigh 2.5 g of Ti3C2T xThe nanosheets were added to 100 mL of deionized water, mechanically stirred for 10 min, and then dispersed in an ice-water bath with ultrasound (60 W) for 1.5 min; then the Ti3C2T x After vortex oscillation (1500 rpm) for 4 min, the aqueous solution was placed in a closed desiccator and evacuated to a vacuum degree of 2000 Pa, and this vacuum degree was maintained for 4 min, and then the air was released. The above evacuation and release process was repeated 12 times to completely remove the bubbles in the aqueous solution. Subsequently, the aqueous solution was continuously extruded through a syringe pump and dripped onto the substrate surface of the coating machine, and the distance between the scraper and the substrate was adjusted to 0.25 mm. The scraper was fixed, and then the substrate unwinding and winding device was started for scraping. The substrate transmission rate was adjusted to 12 cm / min, and the temperature of the heater was 45 °C. The uncrosslinked Ti3C2T x (MXene) film, the MXene film has a thickness of 2.75 ± 0.15 μm, a tensile strength of 276 ± 11 MPa, a Young's modulus of 12.1 ± 0.8 GPa, and a toughness of 3.74 ± 0.28 MJ / m 3 In addition, after 8 weeks of implantation into the skull defect area of rats as a guided bone regeneration membrane, the ratio of the new bone volume to the total volume of the bone defect area was 56.5 ± 1.3%.
[0057] Comparative Example 2
[0058] A 25 mg / mL SS aqueous solution was prepared in advance: 2.5 g of SS powder was weighed and added to 100 mL of deionized water, mechanically stirred for 10 min, and then dispersed in an ice-water bath ultrasound (60 W) for 1.5 min; then the SS aqueous solution was placed in a closed desiccator after vortex oscillation (1500 rpm) for 4 min, evacuated to a vacuum degree of 2000 Pa, and maintained at this vacuum degree for 4 min, and then deflated, and the above evacuation and deflation process was repeated 12 times to completely remove the bubbles in the aqueous solution; then the aqueous solution was continuously extruded and dripped onto the substrate surface of the coating machine through a syringe pump, and the distance between the scraper and the substrate was adjusted to 0.25 mm, the scraper was fixed, and then the substrate unwinding and winding device was started for scraping, the substrate transmission rate was adjusted to 12 cm / min, the temperature of the heater was 45 °C, and the SS film was continuously wound. After the SS film was implanted into the rat skull defect area as a guided bone regeneration film for 8 weeks, the ratio of the new bone volume to the total volume of the bone defect area was 29.1 ± 1.1%.
[0059] Comparative Example 3
[0060] Prepare 25 mg / mL Ti3C2T x Aqueous solution: weigh 2.5 g of Ti3C2T xNanosheets were added to 100 mL of deionized water, mechanically stirred for 10 min, and then dispersed in an ice-water bath with ultrasound (60 W) for 1.5 min; 20 mg / mL ZnCl2 aqueous solution was prepared: 20 g of ZnCl2 was weighed, added to 1000 mL of deionized water, mechanically stirred for 10 min, and then dispersed in an ice-water bath with ultrasound (60 W) for 2 min; then Ti3C2T x After vortex oscillation (1500 rpm) for 4 min, the aqueous solution was placed in a closed desiccator and evacuated to a vacuum degree of 2000 Pa, and this vacuum degree was maintained for 4 min, and then the air was released. The above evacuation and release process was repeated 12 times to completely remove the bubbles in the aqueous solution. Subsequently, the aqueous solution was continuously extruded through a syringe pump and dripped onto the substrate surface of the coating machine, and the distance between the scraper and the substrate was adjusted to 0.25 mm. The scraper was fixed, and then the substrate unwinding and winding devices were started for scraping. The substrate transmission rate was adjusted to 12 cm / min, the temperature of the heater was 45 °C, and the MXene film was continuously wound. Then, the MXene film was immersed in the above-prepared ZnCl2 aqueous solution for 30 min, taken out and soaked and washed with deionized water for 40 min, and then dried in a vacuum oven (45 °C) for 25 min to obtain an IBM composite film. The IBM composite film had a thickness of 2.63 ± 0.12 μm, a tensile strength of 461 ± 12 MPa, and a Young's modulus of 19.0 ± 0.7 GPa, toughness 6.99 ± 0.28 MJ / m 3 In addition, after 8 weeks of implantation into the skull defect area of rats as a guided bone regeneration membrane, the ratio of the new bone volume to the total volume of the bone defect area was 57.8 ± 2.5%.
[0061] As shown in Figure 2, the SBM-II composite film has fewer pores and a denser structure than the MXene film prepared in Comparative Example 1. The infrared spectrum in Figure 3 shows that the SS molecules and Ti3C2T x There are hydrogen bonds between the nanosheets, and Zn 2+ With SS molecules and Ti3C2T x The nanosheets will form ionic cross-links. Due to the stronger interface effect and dense structure, the tensile strength, Young's modulus and toughness of the SBM-II composite film are better than those of the MXene film (Figure 4). xThe nanosheets can synergistically fight inflammation, induce M2 macrophage differentiation, promote osteogenesis, and the barrier properties conferred by the excellent mechanical properties of the SBM-II composite film (preventing fibroblasts from invading the bone defect area). The in vivo bone regeneration performance of the SBM-II composite film is better than that of the MXene film prepared in Comparative Example 1 (Figure 5), the SS film prepared in Comparative Example 2, the HBM film (65.6 ± 2.7%) and the IBM film prepared in Comparative Example 3.
[0062] In summary, the titanium carbide composite film with orderly cross-linked hydrogen bonds and ionic bonds prepared continuously in the present invention not only has high tensile strength (755 MPa), high Young's modulus (32.9 GPa) and high toughness (17.4 MJ / m 3 ), and has excellent in vivo bone regeneration performance. After being implanted into the skull defect area of rats as a guided bone regeneration membrane for 8 weeks, the ratio of the new bone volume to the total volume of the bone defect area was 77.4%. This continuous high-performance titanium carbide composite film has a wide range of applications in aerospace and bone regeneration.
[0063] It should be noted that, according to the above-mentioned embodiments of the present invention, those skilled in the art can fully implement the full scope of the independent claims and dependent rights of the present invention, and the implementation process and method are the same as the above-mentioned embodiments; and the parts not elaborated in detail in the present invention belong to the well-known technology in the field.
[0064] The above descriptions are only some specific implementation methods of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any person familiar with the art within the technical scope disclosed in the present invention should be covered within the protection scope of the present invention.
Claims
1. A continuous preparation method for a high-strength titanium carbide film for guiding bone regeneration, characterized in that: The steps include: (1) Titanium carbide (Ti3C2T x ) and silk sericin (SS) were respectively prepared into uniform Ti3C2T x aqueous solution and SS aqueous solution, the Ti3C2T x The aqueous solution contains Ti3C2T x Nanosheets; (2) The Ti3C2T obtained in step (1) x The aqueous solution and the SS aqueous solution were mixed and vortexed to make SS uniformly adsorbed on the Ti3C2T x The surface of the nanosheets was subjected to uniform mixing of aqueous solutions; (3) vacuum-debubbling the mixed aqueous solution obtained in step (2), and then continuously assembling a hydrogen-bonded cross-linked titanium carbide (HBM) composite film by a roll-to-roll assisted doctor blade coating method; (4) The HBM composite film obtained in step (3) is immersed in a zinc chloride (ZnCl2) aqueous solution, and after washing and drying, a titanium carbide (SBM) composite film with orderly cross-linking of hydrogen bonds and ionic bonds is obtained.
2. The continuous preparation method of a high-strength titanium carbide guided bone regeneration film according to claim 1, characterized in that: In the step (1), Ti3C2T x The concentrations of aqueous solution and SS aqueous solution were both 20–60 mg / mL; Preferably, in step (1), the stirring time is 5 to 15 min, the ultrasonic time is 1 to 2 min, the ultrasonic power is 50 to 70 W, and the ultrasonication is performed in an ice water bath.
3. The continuous preparation method of a high-strength titanium carbide guided bone regeneration film according to claim 1, characterized in that: In the step (2), the Ti3C2T x The mass ratio of nanosheets to SS is 3–20; Preferably, in step (2), the vortex oscillation speed is 1000-2000 rpm, and the time is 3-5 min.
4. The continuous preparation method of a high-strength titanium carbide guided bone regeneration film according to claim 1, characterized in that: In the step (3), the vacuum degassing process is to place the mixed aqueous solution in a closed desiccator, evacuate to a vacuum degree of 1000-3000 Pa, and maintain this vacuum degree for 2-4 minutes, and then release the air, and repeat the above vacuuming and releasing process 10-15 times.
5. The continuous preparation method of a high-strength titanium carbide film for guiding bone regeneration according to claim 1, characterized in that: In the step (3), the specific implementation process of continuously assembling the mixed aqueous solution after vacuum degassing into the HBM composite film by the roll-to-roll assisted scraping method includes: (31) The mixed aqueous solution after vacuum degassing is continuously extruded through a syringe pump and dripped onto the substrate surface of the coating machine; (32) Adjust the distance between the scraper and the substrate to 0.2-3 mm, fix the scraper, and then start the substrate unwinding and winding device for scraping, and the substrate conveying rate is greater than 10 cm / min; (33) The substrate with the mixed aqueous solution coated on its surface is continuously conveyed through a heater at a temperature of 40–50 °C to dry and remove moisture, and then continuously rolled up to obtain an HBM composite film.
6. The method for continuously preparing a high-strength titanium carbide film for guiding bone regeneration according to claim 1, characterized in that: In the step (4), the concentration of the ZnCl2 aqueous solution is 5-100 mg / mL, wherein the preferred concentration range is 10-40 mg / mL, and the soaking time is 20-40 min.
7. The continuous preparation method of a high-strength titanium carbide guided bone regeneration film according to claim 1, characterized in that: In the step (4), the washing process is implemented by soaking in deionized water for 30 to 50 minutes, and the drying process is implemented by vacuum drying at 40 to 50° C. for 20 to 30 minutes.
8. The continuous preparation method of a high-strength titanium carbide film for guiding bone regeneration according to claim 1, characterized in that: In the step (4), the zinc ions (Zn 2+ ) content is 0.4~2.6 wt%.
9. The continuous preparation method of a high-strength titanium carbide guided bone regeneration film according to claim 1, characterized in that: In the step (4), the thickness of the obtained SBM composite film is 1-20 μm.
Citation Information
Cited By
Silk-based double-layer composite guided bone regeneration film and preparation method thereof
CN121371328A
